INVESTIGASI LISTRIK MIKROHIDRO DI PERKEBUNAN GUNUNG PASANG KECAMATAN PANTI, JEMBER - Dedy Eko Rahmanto; Michael Joko Wibowo; Ahmad Fahriannur; Abdul Ghofur (JURNAL AGROTEKNOLOGI, 2022)
Gunung Pasang plantation has a micro-hydro power plant which is used for electricity needs of the factory and the surrounding residents. The micro-hydro power plant is not equipped with an electronic load controller system. The micro-hydro electric voltage can change at any time if there are some changes in consumer load. Micro-hydro electricity investigation is needed to determine the feasibility of the micro-hydro electricity. The investigation was carried out by recording the micro-hydro electricity data which is produced in Gunung Pasang Plantation. Data recording is done by installing a power logger while the micro-hydro turbine operates. The results of the investigation showed that the electric voltage which is generated by Gunung Pasang micro-hydro was fluctuating from less than 100 volts to more than 245 volts with a voltage value that deviated a lot from the 1995 SPLN rule. The average daily voltage which was generated was around 150.34 to 172.18 volts with a standard deviation of 22.11 to 30.67 volts. Micro-hydro operators tried to regulate the work of micro-hydro turbines at all times so the generated voltage could reach the stability. This unstable electrical condition was actually not feasible and had possibility to cause damage to consumer’s electrical equipment. It was necessary to have an electronic load controller system so the outcome of the micro-hydro voltage could be stable and safe. Keywords: investigation, micro-hydro, voltage